Reconfigurable web service integration in the extended logistics enterprise - Talevski, A.; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2005)
Transportation and warehousing logistics are activities that require strong information systems and computer support. This requirement has grown with the advent of e-commerce. Companies such as FedEx and UPS now allow their customers to track and monitor the fulfilment of their requested services on the Internet. In order for such a system to be effective, the goods need to be handled by the one corporation, with an integrated system. This is rare in the case of Small to Medium sized Enterprise (SME). With the advent of Business to Business (B2B), and Partner to Partner (P2P) e-commerce, there has been an increasing tendency for SMEs to set up consortia that represent several players in a given field in order to contend with larger competitors. This paper deals with the concept of an extended logistics enterprise and explores the software engineering issues underlying the development of such complex systems.